The instrumentation for measurements of evoked otoacoustic emissions - RANACHOWSKI, Z. (Archives of Acoustics, 1994)
Evoked Otoacoustic Emissions (EOAEs) are studied by the use of the recently built EOAEs processor. For this purpose 101 dentist students underwent screening earphone audiometry and electrostimulation high-rrequency tests and were tested with use of the EOAEs processor. Three different parameters were evaluated from the recorded waveforms. Great inter- and intraindividual differences within the recordings were observed. The problems concerning the probe fitting are also discussed.